Examining the Relationship Between Health Service Quality and Patient Satisfaction in Cambodian Public Hospitals: A SERVPERF-Based Study - Kosal Thay; Sarom Mok; Mengheang Hor; Somuny Som (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The quality of health services in Cambodia continues to face multiple challenges. Despite ongoing reforms, gaps remain in meeting the expectations of key stakeholders. The purposes of this study were threefold: (1) to find out the level of service quality practice; (2) to determine the relationship between health service quality and patient satisfaction; (3) to examine the effect of each dimension of service quality on patient satisfaction. A quantitative approach was adopted, with structured questionnaires used to collect data, with a reliability between 0.82 and 0.96. A total of 220 patients visiting 11 public hospitals across Cambodia participated in this study, which used a purposive sampling method. The collected data were analyzed using descriptive and inferential statistics in SPSS. The results showed that overall service quality practice was perceived at a high level (M = 4.22, S.D. = 0.60). Among all SERVPERF dimensions, empathy and assurance had the highest mean scores (4.26 and 4.25, respectively), followed by reliability, tangibles, and responsiveness. The results also showed that all dimensions are positively and significantly associated with patient satisfaction at the 0.01 level, with overall correlation coefficients ranging from r = 0.62 to r = 0.89. This finding provides empirical validation of the SERVPERF model in Cambodian public hospitals, with empathy and assurance as key dimensions for enhancing patient satisfaction. Policymakers and health educators working in Cambodia are given recommendations. The Ministry of Health and international health partners may find this study useful.